2020
DOI: 10.1200/jco.2020.38.15_suppl.e19131
|View full text |Cite
|
Sign up to set email alerts
|

Treatment patterns in men with metastatic castration sensitive prostate cancer (mCSPC) in the United States (US).

Abstract: e19131 Background: Given recent advances in treatment options for mCSPC, this study assessed US real-world treatment patterns of mCSPC patients over time. Methods: The Optum Clinformatics Extended DataMart was used to identify men with ≥2 claims for PC, ≥1 claim for metastasis, ≥1 castration sensitivity (CS) indicator (CS diagnosis code [dx]; castration and no prostate-specific antigen [PSA] rise; or hormone/castration naive for ≥18 months [mo] before metastasis). Index (idx) date was the 1st metastasis dx da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 0 publications
3
9
0
3
Order By: Relevance
“…[16][17][18] In line with our study, preliminary results from Ke et al, using a similar study period (2015-2018), indicated that the most common 1L therapy for mCSPC was ADT-only (47%), followed by ADT + docetaxel (8%), ADT + abiraterone (7%), and ADT + NSAA (5%), and that the use of newer therapies had increased yet remained comparatively low. 16,17 Flaig et al found that approximately half of the patients enrolled in a US claims database between 2000 and 2013 received ADT-only, although the study period predated widespread use of docetaxel and NHTs. 18 In both studies, >30% of patients did not receive any pharmacotherapy for mCSPC.…”
Section: Discussionsupporting
confidence: 88%
“…[16][17][18] In line with our study, preliminary results from Ke et al, using a similar study period (2015-2018), indicated that the most common 1L therapy for mCSPC was ADT-only (47%), followed by ADT + docetaxel (8%), ADT + abiraterone (7%), and ADT + NSAA (5%), and that the use of newer therapies had increased yet remained comparatively low. 16,17 Flaig et al found that approximately half of the patients enrolled in a US claims database between 2000 and 2013 received ADT-only, although the study period predated widespread use of docetaxel and NHTs. 18 In both studies, >30% of patients did not receive any pharmacotherapy for mCSPC.…”
Section: Discussionsupporting
confidence: 88%
“…[1][2][3][4] These treatments are now considered standard of care and included in prostate cancer treatment guidelines. [5][6][7] Despite this, new combination treatments with ADT may still be used relatively infrequently, compared with ADT alone, 8,9 owing to concerns about side effects of chemotherapy, prolonged exposure to steroids, the need for patient monitoring, and a lack of long-term follow-up from recently reported studies. Thus, long-term safety data are of interest.…”
Section: Introductionmentioning
confidence: 99%
“…As NHAs have been approved only relatively recently, there are currently few real-world published data assessing NHA use in the mHSPC space [30]; these are restricted to the US, and largely based on data collected prior to NHA approvals for mHSPC. They indicate that, despite the emergence of docetaxel or NHA combination therapies, a large proportion of men continue to be treated with ADT alone [30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%